(untitled) (Eurasian Research Bulletin, 2023)
This article analytically substantiates the opinion that improving the mechanism for levying taxes on individuals has an important role in determining the tax base, and developed appropriate recommendations. The effective implementation of these tasks involves the study of systemic features of the mechanisms, methods and tools that regulate the taxation of individuals, a detailed assessment of various aspects of the taxation of individuals, theoretical and practical aspects of the trends in the development of emerging relations